Somatic Mutations from Whole Exome Sequencing Analysis of the Patients with Biliary Tract Cancer - Kyong-Ah Yoon; Sang Myung Woo; Yun-Hee Kim; Sun-Young Kong; Sung-Sik Han; Sang-Jae Park; Woo Jin Lee (Genomics & Informatics)
Biliary tract cancer (BTC) is a rare cancer and is associated with a poor prognosis. To understand the genetic characteristics of BTC, we analyzed whole-exome sequencing data and identified somatic mutations in patients with BTC. Tumors and matched blood or normal samples were obtained from seven patients with cholangiocarcinoma who underwent surgical resection. We discovered inactivating mutations of tumor suppressor genes, including APC, TP53, and ARID1A, in three patients. Activating mutations of KRAS and NRAS were also identified. Our analyses identified somatic mutations in Korean patients with BTC.